Genome-wide association study of nutrient composition in meat from three two-way crossbred pig populations using whole-genome resequencing - Tang, Jie; Liang, Yan; An, Rui; Luo, Gan; Tao, Xuan; Liu, Pengliang; Gu, Yiren (Frontiers in Veterinary Science, 2026)
Pork is a major source of animal protein for humans, and as living standards have improved, consumer demand has shifted from quantity to quality. Amino acid and fatty acid compositions determine the nutritional value and flavor of pork. However, the genetic mechanisms underlying variation in these parameters have not been fully elucidated. In this study, we quantified 17 amino acids and 42 fatty acids in the longissimus dorsi muscle from three crossbred pig populations, namely Yorkshire × Tibetan (YT), Yorkshire × Neijiang (YN), and Duroc × Tibetan (DT). YT and YN pigs exhibited higher amino acid concentrations, while DT pigs showed elevated fatty acid levels. Subsequently, whole-genome resequencing of 73 pigs identified 24,125,658 high-quality SNPs, among which 146 were significantly associated with fatty acid traits, leading to the identification of 19 candidate genes linked to palmitic acid (i.e., GALNT2, RET, RHOU, PHYHIPL, FAM13C, BICC1, and TAF5L), oleic acid (i.e., ABCB10, LRP1B, ZNF37A, RHOBTB1, HNRNPF, TMEM26, URB2, FXYD4, PGBD5, LOC110256649, and LOC110256821), and total fatty acids (i.e., UBE2E2). Functional annotation revealed that these candidate genes participate primarily in pathways related to lipid metabolism, glucose homeostasis, and energy balance. The identified SNPs and candidate genes provide valuable insights into the genetic architecture of the fatty acid composition in pork and may serve as molecular targets for improving meat quality through breeding.